Toner for electrostatic charge image development
A toner formulation with controlled crystalline and amorphous polyester resin properties addresses the challenge of achieving both high transferability and charging stability by optimizing resin compatibility and circularity distribution.
Patent Information
- Application Number
- JP2024097823
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-06-19
- Filing Date
- 2024-06-18
- Publication Date
- 2025-01-07
AI Technical Summary
Existing toners face challenges in achieving both high transferability and charging stability due to the use of crystalline polyester resins, which can lead to cracking and decreased charging stability when combined with amorphous resins, particularly with high circularity components.
A toner formulation using a combination of crystalline and amorphous polyester resins with specific ester group concentrations and melting points, along with a controlled circularity distribution, is developed to enhance compatibility and maintain both transferability and charging stability.
The toner achieves a wide circularity distribution, ensuring high transferability and charging stability by balancing the properties of the crystalline and amorphous resins, resulting in improved image development performance.
Smart Images

Figure 2025000587000009 
Figure 2025000587000001 
Figure 2025000587000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a toner for developing electrostatic images used for developing latent images formed in electrophotography, electrostatic recording, electrostatic printing and the like, and a method for producing the same. [Background technology]
[0002] In order to improve the transferability, various methods have been investigated for increasing the circularity of toner particles by, for example, a spheronization treatment.
[0003] Patent Document 1 discloses a toner comprising at least a binder resin, a colorant, a release agent and a filler, the binder resin comprising at least a non-crystalline polyester resin and a crystalline polyester resin, and the filler being silica fine particles having an average primary particle diameter of 50 nm or less and having a circularity of 0.960 or more.
[0004] In Patent Document 2, a toner having toner particles containing at least a binder resin, a colorant, and a wax, and an external additive is subjected to a 20 kHz, 50 W / 10 cm 3 When a dispersion liquid in which the toner is dispersed is irradiated with ultrasonic waves of 512×512 pixels (0.37 μm×0.37 μm per pixel) for 5 minutes, the measured value C1 of particles having a size of 0.50 μm or more and 2.00 μm or less as measured by a flow type particle image measuring device with an image processing resolution of 512×512 pixels is 40.0% or less by number, and the surface tension index of the toner with respect to a 45% by volume aqueous methanol solution as measured by a capillary suction time method is 5.0×10 -3 N / m or more 1.0×10 -1 A toner characterized by a viscosity of less than N / m is disclosed. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2020-86288 A [Patent Document 2] JP 2009-294374 A Summary of the Invention [Problem to be solved by the invention]
[0006] On the other hand, the use of a crystalline polyester resin with excellent low-temperature fixing properties in combination with an amorphous polyester resin as a binder resin for toner has been studied, but an amorphous polyester resin obtained using an aliphatic diol with a relatively short carbon chain is more likely to crack than a resin obtained using an aromatic diol such as an alkylene oxide adduct of bisphenol A, and the high circularity component increases during spheronization treatment. Particles with a high circularity have excellent transferability, but have the problem that they are difficult to triboelectrically charge, and therefore the charging stability is easily reduced.
[0007] The present invention relates to a toner for developing electrostatic images, which has excellent transferability and charging stability, and a method for producing the toner. [Means for solving the problem]
[0008] The present invention relates to [1] A toner for developing electrostatic images, comprising a crystalline polyester resin C and an amorphous polyester resin A, wherein the ester group concentration of the crystalline polyester resin C is 6.5 mmol / g or more and 10.0 mmol / g or less and the melting point is 65° C. or more and 105° C. or less, the alcohol component of the amorphous polyester resin A contains 80 mol % or more of an aliphatic diol having 2 to 5 carbon atoms, the average circularity of the toner for developing electrostatic images is 0.955 to 0.975, the relative frequency of the circularity being 0.920 to 0.960 is 30% to 40%, and the relative frequency of the circularity being 0.970 to 0.990 is 25% to 35%; and [2] A method for producing a toner for developing electrostatic images, comprising a crystalline polyester resin C and an amorphous polyester resin A, the crystalline polyester resin C having an ester group concentration of 6.5 mmol / g or more and 10.0 mmol / g or less and a melting point of 65° C. or more and 105° C. or less, the alcohol component of the amorphous polyester resin A containing 80 mol % or more of a diol having 2 to 5 carbon atoms, the toner for developing electrostatic images having an average circularity of 0.955 to 0.975 or less, a relative frequency of a circularity of 0.920 to 0.960 or less being 30% to 40%, and a relative frequency of a circularity of 0.970 to 0.990 or less being 25% to 35%, the method comprising the steps of: melt-kneading a mixture containing the crystalline polyester resin C and the amorphous polyester resin A; pulverizing the kneaded mixture; classifying the pulverized product; and subjecting the classified product to a hot air treatment. Regarding. Effect of the Invention
[0009] The toner for developing electrostatic images of the present invention exhibits excellent effects in terms of transferability and charge stability. [Brief description of the drawings]
[0010] [Figure 1] 4 is a graph showing the distribution of circularity of the toners obtained in Example 1, Comparative Example 4, and Comparative Example 5 in the examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The toner for developing electrostatic images of the present invention is characterized by a wide circularity distribution. As a result, particles with a high circularity that are excellent in transferability and particles with a low circularity that are easily triboelectrically charged are appropriately mixed, making it possible to achieve a high level of both transferability and charging stability. Furthermore, by combining an amorphous polyester resin (amorphous polyester resin A) obtained by using an aliphatic diol with a relatively short carbon chain with a crystalline polyester resin (crystalline polyester resin C) whose ester group concentration and melting point are adjusted, a wide circularity distribution can be realized even when the average circularity is increased to a predetermined range. This is presumably because the crystalline polyester resin is in an appropriate compatible state with the amorphous polyester resin in a good balance of hydrophilicity and hydrophobicity, which improves the mixability as a binder resin composition and appropriately improves the toughness of the entire resin, making it possible to increase the average circularity while maintaining a wide circularity distribution.
[0012] The average circularity of the toner of the present invention is 0.955 or more, preferably 0.957 or more, more preferably 0.960 or more, from the viewpoint of transferability, and is 0.975 or less, preferably 0.973 or less, more preferably 0.970 or less, from the viewpoint of charging stability.
[0013] The relative frequency (proportion of frequency) of the circularity of 0.920 or more and 0.960 or less is 30% or more, preferably 31% or more, more preferably 32% or more, from the viewpoint of charging stability, and is 40% or less, preferably 39% or less, more preferably 38% or less, from the viewpoint of transferability.
[0014] The relative frequency of the circularity of 0.970 or more and 0.990 or less is 25% or more, preferably 26% or more, more preferably 27% or more, from the viewpoint of transferability, and is 35% or less, preferably 34% or less, more preferably 33% or less, from the viewpoint of charging stability.
[0015] From the viewpoint of compatibility with the amorphous polyester resin A, the ester group concentration of the crystalline polyester resin C is 6.5 mmol / g or more, preferably 6.6 mmol / g or more, more preferably 6.8 mmol / g or more, and is 10.0 mmol / g or less, preferably 9.5 mmol / g or less, more preferably 9.0 mmol / g or less.
[0016] The ester group concentration of the crystalline polyester resin C is calculated by the following formula.
[0017]
number
[0018] (In the formula, A is the total amount (mol) of ester bonds produced when all the raw material monomers of the polyester resin are reacted, and B is the total mass (g) of the raw material monomers constituting the polyester resin. The numbers in parentheses in the formula indicate the units of each value.)
[0019] From the viewpoint of compatibility with the amorphous polyester resin A, the melting point of the crystalline polyester resin C is 65°C or higher, preferably 67°C or higher, more preferably 70°C or higher, and 105°C or lower, preferably 100°C or lower, more preferably 95°C or lower.
[0020] The crystallinity of a resin is represented by a crystallinity index defined as the ratio of the softening point to the maximum endothermic peak temperature measured by a differential scanning calorimeter, that is, the value of [softening point / maximum endothermic peak temperature]. The crystalline resin is a resin having a crystallinity index of 0.6 or more, preferably 0.7 or more, more preferably 0.9 or more, and 1.4 or less, preferably 1.2 or less, more preferably 1.1 or less. On the other hand, an amorphous resin is a resin in which no endothermic peak is observed, or if an endothermic peak is observed, the crystallinity index is greater than 1.4, preferably greater than 1.5, more preferably 1.6 or more, or less than 0.6, preferably 0.5 or less. The crystallinity of the resin can be adjusted by the type and ratio of the raw material monomers, and the production conditions (e.g., reaction temperature, reaction time, cooling rate), etc. The maximum endothermic peak temperature refers to the temperature of the peak with the largest peak area among the observed endothermic peaks. In the case of a crystalline resin, the maximum endothermic peak temperature is the melting point.
[0021] The crystalline polyester resin C is preferably a polycondensate of an alcohol component containing an aliphatic diol and a carboxylic acid component containing an aliphatic dicarboxylic acid compound.
[0022] Examples of the aliphatic diol include ethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, and 1,12-dodecanediol. Of these, ethylene glycol is preferred from the viewpoints of the ester group concentration and the melting point.
[0023] From the viewpoint of achieving appropriate compatibility with the amorphous polyester resin A, the carbon number of the aliphatic diol is preferably 2 or more and preferably 12 or less, more preferably 10 or less, even more preferably 6 or less, and still more preferably 3 or less.
[0024] From the viewpoint of improving the low-temperature fixing property of the toner, the aliphatic diol preferably has a hydroxyl group at the end of the carbon chain, and is more preferably an α,ω-straight-chain alkanediol.
[0025] The content of the aliphatic diol in the alcohol component is preferably 80 mol % or more, more preferably 90 mol % or more, and further preferably 95 mol % or more, and 100 mol % or less.
[0026] Examples of other alcohol components include aromatic diols such as bisphenol A and alkylene oxide adducts of bisphenol A, hydrogenated bisphenol A, trihydric or higher alcohols such as sorbitol, pentaerythritol, glycerin, and trimethylolpropane.
[0027] Examples of the aliphatic dicarboxylic acid compound include succinic acid (carbon number: 4), fumaric acid (carbon number: 4), adipic acid (carbon number: 6), suberic acid (carbon number: 8), azelaic acid (carbon number: 9), sebacic acid (carbon number: 10), dodecanedioic acid (carbon number: 12), tetradecanedioic acid (carbon number: 14), succinic acid having an alkyl group or an alkenyl group on the side chain, anhydrides of these acids, and alkyl esters of these acids having a carbon number of 1 to 3. Here, when the aliphatic dicarboxylic acid compound is an alkyl ester, the carbon number of the alkyl group is not included in the above carbon number.
[0028] From the viewpoint of achieving adequate compatibility with the amorphous polyester resin A, the carbon number of the aliphatic dicarboxylic acid compound is preferably 4 or more, more preferably 8 or more, even more preferably 10 or more, and even more preferably 12 or more, and is preferably 16 or less, more preferably 14 or less.
[0029] The aliphatic dicarboxylic acid compound may be a saturated aliphatic dicarboxylic acid compound or an unsaturated aliphatic dicarboxylic acid compound, but from the viewpoint of achieving adequate compatibility with the amorphous polyester resin A, it is preferable that it is a saturated aliphatic dicarboxylic acid compound.
[0030] The content of the aliphatic dicarboxylic acid compound in the carboxylic acid component is preferably 65 mol % or more, more preferably 70 mol % or more, and further preferably 75 mol % or more, and 100 mol % or less.
[0031] Examples of other carboxylic acid components include aromatic dicarboxylic acid compounds such as phthalic acid, isophthalic acid, and terephthalic acid, and trivalent or higher carboxylic acid compounds such as trimellitic acid and pyromellitic acid.
[0032] The alcohol component may appropriately contain a monohydric alcohol, and the carboxylic acid component may appropriately contain a monovalent carboxylic acid compound.
[0033] In this specification, macromonomers and hydroxycarboxylic acids are not included in the alcohol component and carboxylic acid component.
[0034] The equivalent ratio of the carboxy group of the carboxylic acid component to the hydroxyl group of the alcohol component (COOH group / OH group) is preferably 0.8 or more, more preferably 0.9 or more, from the viewpoint of charging stability, and is preferably 1.2 or less, more preferably 1.1 or less, from the viewpoint of low-temperature fixing property.
[0035] The crystalline polyester resin C can be produced, for example, by polycondensing an alcohol component and a carboxylic acid component in an inert gas atmosphere, preferably in the presence of an esterification catalyst, and if necessary, in the presence of an esterification promoter, a polymerization inhibitor, etc., at a temperature preferably of 120°C or higher and 230°C or lower.
[0036] Examples of the esterification catalyst include tin compounds such as dibutyltin oxide and tin(II) 2-ethylhexanoate, and titanium compounds such as titanium diisopropoxybis(triethanolaminate) and titanium dihydroxybis(triethanolaminate). The amount of the esterification catalyst used is preferably 0.01 parts by mass or more, more preferably 0.1 parts by mass or more, and preferably 1.5 parts by mass or less, more preferably 1 part by mass or less, based on 100 parts by mass of the total amount of the alcohol component and the carboxylic acid component. Examples of the esterification promoter include gallic acid. The amount of the esterification promoter used is preferably 0.001 parts by mass or more, more preferably 0.01 parts by mass or more, and preferably 0.5 parts by mass or less, more preferably 0.1 parts by mass or less, based on 100 parts by mass of the total amount of the alcohol component and the carboxylic acid component. Examples of the polymerization inhibitor include tert-butylcatechol. The amount of the polymerization inhibitor used is preferably 0.001 part by mass or more, more preferably 0.01 part by mass or more, and preferably 0.5 part by mass or less, more preferably 0.1 part by mass or less, per 100 parts by mass of the total amount of the alcohol component and the carboxylic acid component.
[0037] In the present invention, the polyester resin may be modified to such an extent that its properties are not substantially impaired. Examples of modified polyester resins include polyester resins grafted or blocked with phenol, urethane, epoxy, or the like by the methods described in JP-A-11-133668, JP-A-10-239903, JP-A-8-20636, etc., and among the modified polyester resins, urethane-modified polyester resins in which polyester resins are urethane-extended with a polyisocyanate compound are preferred.
[0038] From the viewpoint of achieving adequate compatibility with the amorphous polyester resin A, the softening point of the crystalline polyester resin C is preferably 50°C or higher, more preferably 60°C or higher, and even more preferably 65°C or higher, and is preferably 110°C or lower, more preferably 105°C or lower, and even more preferably 100°C or lower.
[0039] The acid value of the crystalline polyester resin C is preferably 1 mgKOH / g or more, more preferably 3 mgKOH / g or more, from the viewpoint of low-temperature fixing property, and is preferably 20 mgKOH / g or less, more preferably 15 mgKOH / g or less, from the viewpoint of charging stability.
[0040] The content of crystalline polyester resin C in the total amount of crystalline polyester resin C and amorphous polyester resin A is preferably 3 mass% or more, more preferably 4 mass% or more, and even more preferably 5 mass% or more from the viewpoint of transferability, and is preferably 30 mass% or less, more preferably 25 mass% or less, and even more preferably 20 mass% or less from the viewpoint of charging stability.
[0041] The amorphous polyester resin A is an alcohol component containing 80 mol % or more of an aliphatic diol having 2 to 5 carbon atoms, i.e., a polycondensation product of an alcohol component containing 80 mol % or more of an aliphatic diol having 2 to 5 carbon atoms and a carboxylic acid component.
[0042] Examples of the aliphatic diol having 2 to 5 carbon atoms include ethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,2-butanediol, 1,3-butanediol, 1,4-butanediol, 2,3-butanediol, 1,2-pentanediol, 1,3-pentanediol, 1,4-pentanediol, 1,5-pentanediol, 2,3-pentanediol, 2,4-pentanediol, 1,4-butenediol, and neopentyl glycol.
[0043] From the viewpoint of transferability and charging stability, the alcohol component of the amorphous polyester resin A preferably contains ethylene glycol and neopentyl glycol. The molar ratio of ethylene glycol to neopentyl glycol (ethylene glycol / neopentyl glycol) is preferably 10 / 90 or more, more preferably 30 / 70 or more, even more preferably 50 / 50 or more, and is preferably 90 / 10 or less, more preferably 80 / 20 or less, even more preferably 70 / 30 or less. Here, ethylene glycol also includes those derived from polyethylene terephthalate, as described later.
[0044] The content of the aliphatic diol having 2 to 5 carbon atoms is 80 mol % or more, preferably 90 mol % or more, more preferably 95 mol % or more and 100 mol % or less in the alcohol component from the viewpoint of transferability and charging stability. When two or more resins are used in combination as the amorphous polyester resin, the content of the aliphatic diol is the weighted average value calculated based on the content of the aliphatic diol used in each resin in the alcohol component in accordance with the mass ratio of the resin.
[0045] Examples of other alcohol components include aliphatic diols having 6 or more carbon atoms, aromatic diols such as bisphenol A and alkylene oxide adducts of bisphenol A, hydrogenated bisphenol A, sorbitol, pentaerythritol, glycerin, trimethylolpropane, and other trihydric or higher alcohols.
[0046] The carboxylic acid component preferably contains an aromatic dicarboxylic acid compound.
[0047] Examples of the aromatic dicarboxylic acid compound include phthalic acid, isophthalic acid, terephthalic acid, anhydrides of these acids, and alkyl esters of these acids having 1 to 3 carbon atoms.
[0048] From the viewpoint of transferability and charging stability, the carboxylic acid component of the amorphous polyester resin A preferably contains two or more kinds selected from the group consisting of terephthalic acid or terephthalic acid alkyl esters having a carbon number of 1 to 3 in the alkyl group, isophthalic acid or isophthalic acid alkyl esters having a carbon number of 1 to 3 in the alkyl group, and phthalic acid or phthalic acid alkyl esters having a carbon number of 1 to 3 in the alkyl group, and more preferably contains two kinds. Among them, from the viewpoint of transferability, a combination of terephthalic acid or its alkyl ester and isophthalic acid or its alkyl ester is preferred, and the molar ratio of terephthalic acid to isophthalic acid (terephthalic acid / isophthalic acid) is preferably 5 / 95 or more, more preferably 20 / 80 or more, even more preferably 30 / 70 or more, even more preferably 50 / 50 or more, even more preferably 60 / 40 or more, and preferably 95 / 5 or less, more preferably 85 / 15 or less, even more preferably 80 / 20 or less.
[0049] From the viewpoints of transferability and charging stability, the content of the aromatic dicarboxylic acid compound in the carboxylic acid component is preferably 80 mol % or more, more preferably 90 mol % or more, and even more preferably 95 mol % or more, and 100 mol % or less.
[0050] Examples of the carboxylic acid component other than the aromatic dicarboxylic acid compound include an aliphatic dicarboxylic acid compound and a trivalent or higher carboxylic acid compound.
[0051] Examples of the aliphatic dicarboxylic acid compounds include aliphatic dicarboxylic acids such as oxalic acid, malonic acid, maleic acid, fumaric acid, citraconic acid, itaconic acid, glutaconic acid, succinic acid which may be substituted with a hydrocarbon group having from 1 to 20 carbon atoms, and adipic acid, anhydrides of these acids, and alkyl esters in which the alkyl group has from 1 to 3 carbon atoms.
[0052] Examples of the trivalent or higher carboxylic acid compound include trimellitic acid, pyromellitic acid, anhydrides of these acids, and alkyl esters of these acids having 1 to 3 carbon atoms.
[0053] In order to adjust the softening point, trivalent or higher raw material monomers may be used for the alcohol component and / or carboxylic acid component of the amorphous polyester resin A. In this case, in order to improve transferability, it is preferable to use a trivalent or higher alcohol, preferably glycerin or trimethylolpropane, more preferably glycerin. The content of the trivalent or higher alcohol in the alcohol component is preferably 1 mol% or more, more preferably 3 mol% or more, and preferably 20 mol% or less, more preferably 15 mol% or less.
[0054] In addition to the alcohol component and the carboxylic acid component, polyethylene terephthalate (PET) may be used. PET, or ethylene glycol and terephthalic acid produced by depolymerization of a portion of it, are used as raw material monomers in a polycondensation reaction and are incorporated into polyester resin. PET is an equimolar polycondensation product of ethylene glycol and terephthalic acid, and the ethylene glycol and terephthalic acid that make up PET are regarded as the alcohol component and the carboxylic acid component, respectively.
[0055] The PET may be new PET (virgin PET) or recycled PET. Recycled PET is made by collecting used PET, washing it as necessary, and separating it from other materials before crushing it. The crushed material is then depolymerized to break it down into monomer units, which are then used to resynthesize the material.
[0056] The IV value of PET is preferably 0.40 or more, more preferably 0.45 or more, even more preferably 0.50 or more, and even more preferably 0.55 or more, and from the viewpoint of low-temperature fixability and uniform depolymerization, it is preferably 0.85 or less, more preferably 0.80 or less, even more preferably 0.75 or less, and even more preferably 0.70 or less. The IV value is an intrinsic viscosity and is an index of molecular weight.
[0057] Commercially available PET products with an IV value of 0.40 or more and 0.85 or less include RAMAPET L1 (manufactured by Indorama Ventures, IV value: 0.60), RAMAPET BF3067 (manufactured by Indorama Ventures, IV value: 0.65), RAMAPET N2G (manufactured by Indorama Ventures, IV value: 0.75), TRN-NTJ (manufactured by Teijin Limited, IV value: 0.53), TRN-RTJC (manufactured by Teijin Limited, IV value: 0.64), RAMAPET S1 (manufactured by Indorama Ventures, IV value: 0.84), and UK-31 (manufactured by Utsumi Recycle Systems Co., Ltd., IV value: 0.67).
[0058] The content of the low IV value PET in the total amount of PET subjected to polycondensation is preferably 90 mass % or more, more preferably 95 mass % or more, and further preferably 98 mass % or more, and 100 mass % or less.
[0059] The PET content is preferably 5 mol% or more, more preferably 10 mol% or more, even more preferably 20 mol% or more, and even more preferably 25 mol% or more, and is preferably 75 mol% or less, more preferably 50 mol% or less, and even more preferably 40 mol% or less, in the total amount of the alcohol component, the carboxylic acid component, and the PET, from the viewpoint of durability. When the amorphous polyester resin A is composed of two or more resins, the weighted average value of the PET contents of the respective resins is defined as the PET content of the amorphous polyester resin A. In addition, since PET is an equimolar polycondensation product of ethylene glycol, terephthalic acid, dimethyl terephthalate, etc., the terephthalic acid-ethylene glycol unit (Mw: 192) is calculated as 1 mole. Therefore, the number of moles of PET = the number of moles of ethylene glycol units = the number of moles of terephthalic acid units.
[0060] The alcohol component may appropriately contain a monohydric alcohol, and the carboxylic acid component may appropriately contain a monovalent carboxylic acid compound.
[0061] From the viewpoint of adjusting the softening point of the polyester resin, the equivalent ratio (COOH group / OH group) of the carboxy group of the carboxylic acid component (including the terephthalic acid unit in the PET) to the hydroxyl group of the alcohol component (including the ethylene glycol unit in the PET) is preferably 0.6 or more, more preferably 0.7 or more, even more preferably 0.75 or more, and is preferably 1.2 or less, more preferably 1.15 or less.
[0062] The polycondensation reaction conditions of the alcohol component and the carboxylic acid component of the amorphous polyester resin are similar to those of the crystalline polyester resin, except that the suitable reaction temperature is preferably 130°C or more, more preferably 170°C or more, and preferably 250°C or less, more preferably 240°C or less.
[0063] The softening point of the amorphous polyester resin A is preferably 80° C. or higher, more preferably 90° C. or higher, from the viewpoint of charging stability, and is preferably 150° C. or lower, more preferably 140° C. or lower, from the viewpoint of low-temperature fixing property and transferability.
[0064] From the viewpoints of low-temperature fixability and fixing width, the amorphous polyester resin A may be composed of resins having different softening points. The difference in softening point between the two resins is preferably 5° C. or more, more preferably 10° C. or more, and is preferably 60° C. or less, more preferably 30° C. or less, and even more preferably 20° C. or less.
[0065] The softening point of the amorphous polyester resin having a higher softening point (resin AH) is preferably 90°C or higher, more preferably 100°C or higher, from the viewpoint of fixing width, and is preferably 150°C or lower, more preferably 140°C or lower, from the viewpoint of low-temperature fixing property and transferability.
[0066] Furthermore, the softening point of the amorphous polyester resin (resin AL) having a lower softening point is preferably 80° C. or higher, more preferably 90° C. or higher, from the viewpoint of charging stability, and is preferably 120° C. or lower, more preferably 110° C. or lower, from the viewpoint of low-temperature fixing property and transferability.
[0067] The mass ratio of resin AH to resin AL (resin AH / resin AL) is preferably 10 / 90 or more, more preferably 20 / 80 or more, even more preferably 30 / 70 or more, and is preferably 90 / 10 or less, more preferably 80 / 20 or less, even more preferably 70 / 30 or less.
[0068] The glass transition temperature of the amorphous polyester resin A is preferably 40° C. or higher, more preferably 50° C. or higher, from the viewpoint of charging stability, and is preferably 80° C. or lower, more preferably 70° C. or lower, and even more preferably 65° C. or lower, from the viewpoint of low-temperature fixing property and transferability.
[0069] From the viewpoint of transferability, the acid value of the amorphous polyester resin A is preferably 3 mgKOH / g or more, more preferably 5 mgKOH / g or more, and from the viewpoint of charging stability, it is preferably 40 mgKOH / g or less, more preferably 30 mgKOH / g or less.
[0070] The number average molecular weight of the amorphous polyester resin A is preferably 1,000 or more, more preferably 1,500 or more, and even more preferably 2,000 or more from the viewpoint of charging stability, and is preferably 6,000 or less, more preferably 5,000 or less, and even more preferably 4,000 or less from the viewpoint of low-temperature fixing property and transferability.
[0071] The weight average molecular weight of the amorphous polyester resin A is preferably 4,000 or more, more preferably 6,000 or more, and even more preferably 8,000 or more, from the viewpoint of charging stability, and is preferably 500,000 or less, more preferably 200,000 or less, more preferably 100,000 or less, and even more preferably 30,000 or less, from the viewpoint of low-temperature fixing property and transferability.
[0072] The mass ratio of crystalline polyester resin C to amorphous polyester resin A (crystalline polyester resin C / amorphous polyester resin A) is preferably 3 / 97 or more, more preferably 4 / 96 or more, and even more preferably 5 / 95 or more from the viewpoint of low-temperature fixability, and is preferably 30 / 70 or less, more preferably 25 / 75 or less, and even more preferably 20 / 80 or less from the viewpoint of charging stability and transferability.
[0073] In the toner, the crystalline polyester resin C and the amorphous polyester resin A are contained as binder resins.
[0074] Other examples of the binder resin include vinyl resins such as styrene-acrylic resin, epoxy resin, polycarbonate, polyurethane, and composite resins containing two or more of these resins.
[0075] The total content of the crystalline polyester resin C and the amorphous polyester resin A in the binder resin is preferably 70% by mass or more, more preferably 80% by mass or more, even more preferably 90% by mass or more, even more preferably 95% by mass or more, and even more preferably 100% by mass.
[0076] In addition, the content of the binder resin in the toner is preferably 60% by mass or more, more preferably 70% by mass or more, even more preferably 80% by mass or more, and is preferably less than 100% by mass, more preferably 98% by mass or less, even more preferably 95% by mass or less.
[0077] The toner for developing electrostatic images of the present invention may contain additives such as a colorant, a release agent, a charge control agent, a magnetic powder, a flowability improver, a conductivity adjuster, a reinforcing filler such as a fibrous substance, an antioxidant, and a cleaning property improver, in addition to the binder resin.
[0078] As the colorant, dyes, pigments, magnetic materials, etc. used as colorants for toners can be used. For example, carbon black, phthalocyanine blue, permanent brown FG, brilliant fast scarlet, pigment red 122, pigment green B, rhodamine-B base, solvent red 49, solvent red 146, solvent blue 35, quinacridone, carmine 6B, isoindoline, disazo yellow, etc. can be mentioned. In the present invention, the toner may be either a black toner or a color toner.
[0079] From the viewpoint of improving the image density and low-temperature fixability of the toner, the content of the colorant is preferably 1 part by mass or more, more preferably 2 parts by mass or more, and preferably 40 parts by mass or less, more preferably 20 parts by mass or less, and even more preferably 10 parts by mass or less, relative to 100 parts by mass of the binder resin.
[0080] Examples of the release agent include hydrocarbon waxes such as polypropylene wax, polyethylene wax, ethylene propylene copolymer wax, microcrystalline wax, paraffin wax, and Fischer-Tropsch wax, and oxides thereof; ester waxes such as carnauba wax, montan wax, and deacidified waxes thereof, and fatty acid ester wax; fatty acid amides, fatty acids, higher alcohols, and fatty acid metal salts. These may be used alone or in combination of two or more.
[0081] The melting point of the release agent is preferably 60° C. or higher, more preferably 70° C. or higher, from the viewpoint of durability, and is preferably 160° C. or lower, more preferably 140° C. or lower, even more preferably 120° C. or lower, and even more preferably 110° C. or lower, from the viewpoint of low-temperature fixability.
[0082] The content of the release agent is, from the viewpoint of low-temperature fixing property and transfer property of the toner and from the viewpoint of dispersibility in the binder resin, preferably 0.5 parts by mass or more, more preferably 1 part by mass or more, even more preferably 1.5 parts by mass or more, and is preferably 10 parts by mass or less, more preferably 8 parts by mass or less, even more preferably 7 parts by mass or less, relative to 100 parts by mass of the binder resin.
[0083] The charge control agent is not particularly limited, and may contain either a positively chargeable charge control agent or a negatively chargeable charge control agent.
[0084] Examples of the positively charged charge control agent include nigrosine dyes such as "Nigrosine Base EX", "Oil Black BS", "Oil Black SO", "Bontron N-01", "Bontron N-04", "Bontron N-07", "Bontron N-09", and "Bontron N-11" (all manufactured by Orient Chemical Industries Co., Ltd.); triphenylmethane dyes containing a tertiary amine as a side chain; quaternary ammonium salt compounds such as "Bontron P-51" (manufactured by Orient Chemical Industries Co., Ltd.), cetyltrimethylammonium bromide, and "COPY CHARGE PX Examples of such resins include "VP435" (manufactured by Clariant), etc.; polyamine resins, such as "AFP-B" (manufactured by Orient Chemical Industry Co., Ltd.); imidazole derivatives, such as "PLZ-2001" and "PLZ-8001" (both manufactured by Shikoku Kasei Corporation); and styrene-acrylic resins, such as "FCA-701PT" and "FCA-201-PS" (manufactured by Fujikura Kasei Co., Ltd.).
[0085] Examples of the negatively chargeable charge control agent include metal-containing azo dyes such as "Varifast Black 3804", "Bontron S-31", "Bontron S-32", "Bontron S-34", and "Bontron S-36" (all manufactured by Orient Chemical Industry Co., Ltd.), "Aizenspiron Black TRH", and "T-77" (manufactured by Hodogaya Chemical Industry Co., Ltd.); metal compounds of benzilic acid compounds such as "LR-147" and "LR-297" (all manufactured by Nippon Carlit Co., Ltd.); metal compounds of salicylic acid compounds such as "Bontron E-81", "Bontron E-84", "Bontron E-88", and "Bontron E-304" (all manufactured by Orient Chemical Industry Co., Ltd.), and "TN-105" (manufactured by Hodogaya Chemical Industry Co., Ltd.); copper phthalocyanine dyes; and quaternary ammonium salts such as "COPY CHARGE NX VP434 (Clariant), nitroimidazole derivatives, and organometallic compounds.
[0086] From the viewpoint of the charging stability of the toner, the content of the charge control agent is preferably 0.01 parts by mass or more, more preferably 0.2 parts by mass or more, and preferably 10 parts by mass or less, more preferably 5 parts by mass or less, relative to 100 parts by mass of the binder resin.
[0087] The toner for developing electrostatic images of the present invention can be produced by any of the conventionally known methods such as the melt-kneading method, the emulsion aggregation method, the polymerization method, etc., but in the present invention, since the toughness of the resin as a whole is appropriately improved, the toner particles do not break too much even after the pulverization and spheronization steps, and the effect of the combination of the crystalline polyester resin C and the amorphous polyester resin A is more significantly exhibited, it is preferable to produce the toner by subjecting the toner particles obtained by the melt-kneading method to a spheronization treatment. The spheronization treatment includes mechanical surface treatment (mechanical treatment) and thermal surface treatment (hot air treatment), and the latter is preferable since it gives toner particles with a higher circularity. Therefore, the toner particles of the electrostatic image developing toner of the present invention are preferably hot air treated products, and specifically, the toner of the present invention is preferably produced by a method including a step of melting and kneading a mixture containing crystalline polyester resin C and amorphous polyester resin A, and further additives such as a colorant, a release agent, and a charge control agent as necessary (melt kneading step), a step of pulverizing the kneaded product obtained (pulverizing step), a step of classifying the pulverized product obtained (classifying step), and a step of hot air treating the classified product obtained (hot air treatment step). In addition, the toner of the present invention can be obtained by adjusting the average circularity and the distribution of circularity by producing and mixing toners with low and high average circularity by emulsion aggregation method or polymerization method, respectively, but from the viewpoint of transferability, the method including the hot air treatment step is preferable.
[0088] The mixture to be melt-kneaded may be kneaded all at once or in portions, but it is preferable to mix the mixture in advance in a mixer such as a Henschel mixer or a ball mill and then supply the mixture to the kneader.
[0089] The melt kneading can be carried out using a known kneader such as an internal kneader, a single-screw or twin-screw extruder, or an open roll type kneader. From the viewpoint of transferability, it is preferable to use a twin-screw extruder.
[0090] After the melt kneading, the kneaded product is appropriately cooled until it reaches a pulverizable hardness, and then the pulverization step is performed. Here, "cooling" refers to cooling the kneaded product to 0°C or higher and 50°C or lower, or to the glass transition temperature of the binder resin in the kneaded product or lower.
[0091] In the pulverization step, the kneaded material may be pulverized to the desired particle size all at once or in stages. From the viewpoint of efficient and more uniform pulverization, however, it is preferable to carry out the pulverization in two stages: coarse pulverization and fine pulverization.
[0092] Examples of the crushing machine used for the coarse crushing include a hammer mill, a cutter mill, an atomizer, and a rotoplex.
[0093] Examples of the pulverizer used for fine pulverization include jet mills such as a fluidized bed jet mill and an impact plate jet mill, and mechanical mills.
[0094] The degree of pulverization is preferably adjusted appropriately depending on the desired particle size of the toner particles.
[0095] Examples of classifiers used for classification include airflow classifiers, inertial classifiers, sieve classifiers, etc. In the classification step, the pulverized material removed due to insufficient pulverization may be subjected to the pulverization step again, and the pulverization step and the classification step may be repeated as necessary.
[0096] In the hot air spheronizing device used in the hot air treatment process, before the particles are treated with hot air to be spheronized, air is supplied from a secondary air injection nozzle and the pre-treated particles are collided with a collision member to prevent aggregation of the particles before the hot air treatment (pre-treated particles).Then, after the pre-treated particles are spheronized with hot air to form toner particles, the toner particles are cooled with cooling air to prevent thermal fusion between the toner particles.
[0097] The amount of air supplied from the secondary air injection nozzle is preferably 200 L or more per minute in order to prevent the untreated particles from agglomerating, and is preferably 250 L or less in order to prevent the untreated particles from being excessively damaged by the collision member.
[0098] The amount of hot air supplied is preferably 700 L or more, more preferably 800 L or more, per minute from the viewpoint of carrying out sufficient spheronization treatment, and is preferably 1500 L or less, more preferably 1200 L or less, per minute from the viewpoint of preventing untreated particles from melting more than necessary.
[0099] The temperature of the hot air is preferably 50°C or higher, more preferably 70°C or higher, from the viewpoint of avoiding prolonged spheronization treatment, and is preferably 250°C or lower, more preferably 220°C or lower, from the viewpoint of preventing untreated particles from melting more than necessary.
[0100] The supply pressure of the cooling air is preferably 0.1 MPa or more from the viewpoint of avoiding a long cooling treatment time, and is preferably 0.3 MPa or less, more preferably 0.2 MPa or less, from the viewpoint of performing the cooling treatment sufficiently.
[0101] An example of a hot air type sphering device is Meteor Rainbow (manufactured by Nippon Pneumatic Mfg. Co., Ltd.).
[0102] The toner of the present invention preferably further contains an external additive in order to improve transferability. Examples of the external additive include inorganic fine particles such as silica, alumina, titania, zirconia, tin oxide, and zinc oxide, and organic fine particles such as melamine resin fine particles and polytetrafluoroethylene resin fine particles, and two or more of them may be used in combination. Among these, silica is preferred, and from the viewpoint of the transferability of the toner, hydrophobic silica that has been hydrophobized is more preferred.
[0103] Examples of hydrophobic treatment agents for hydrophobizing the surface of silica particles include hexamethyldisilazane (HMDS), dimethyldichlorosilane (DMDS), cyclic silazane, silicone oil, aminosilane, octyltriethoxysilane (OTES), and methyltriethoxysilane.
[0104] From the viewpoint of the chargeability, fluidity, and transferability of the toner, the average particle size of the external additive is preferably 10 nm or more, more preferably 15 nm or more, and is preferably 250 nm or less, more preferably 200 nm or less, and even more preferably 90 nm or less.
[0105] The external addition treatment by mixing the toner particles with the external additives can be carried out according to a conventional method, and a mixer such as a Henschel mixer can be used.
[0106] From the viewpoint of the electrostatic chargeability, fluidity, and transferability of the toner, the content of the external additive is preferably 0.05 parts by mass or more, more preferably 0.1 parts by mass or more, and even more preferably 0.3 parts by mass or more, relative to 100 parts by mass of the toner particles before being treated with the external additive, and is preferably 5 parts by mass or less, and more preferably 4 parts by mass or less.
[0107] The volume median particle size (D 50 ) is preferably 3 μm or more, more preferably 4 μm or more, and is preferably 15 μm or less, more preferably 10 μm or less. 50 ) refers to the particle size at which the cumulative volume frequency calculated by volume fraction is 50% calculated from the smallest particle size. In addition, when the toner is treated with an external additive, the volume median particle size of the toner particles before treatment with the external additive is regarded as the volume median particle size of the toner.
[0108] The toner of the present invention can be used as it is as a toner for one-component development, or as a toner for two-component development mixed with a carrier, in an image forming apparatus of a one-component development system or a two-component development system, respectively. EXAMPLES
[0109] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. Physical properties of resins and the like can be measured by the following methods.
[0110] [Softening point of resin] Using a flow tester "CFT-500D" (Shimadzu Corporation), 1g of sample is heated at a temperature increase rate of 6℃ / min while applying a load of 1.96MPa with the plunger, and extruding the sample from a nozzle with a diameter of 1mm and a length of 1mm. The amount of plunger descent of the flow tester is plotted against the temperature, and the temperature at which half of the sample has flowed out is taken as the softening point.
[0111] [Maximum endothermic peak temperature of resin] Using a differential scanning calorimeter "Q-100" (manufactured by TA Instruments Japan Co., Ltd.), 0.01 to 0.02 g of sample is weighed into an aluminum pan, cooled from room temperature (25°C) to 0°C at a rate of 10°C / min, and maintained at 0°C for 1 minute. After that, the temperature is increased to 180°C at a rate of 10°C / min while performing measurements. The temperature of the peak with the largest peak area among the observed endothermic peaks is regarded as the maximum endothermic peak temperature. For crystalline resins, the maximum endothermic peak temperature is regarded as the melting point.
[0112] [Glass transition temperature of resin] Using a differential scanning calorimeter "Q-100" (manufactured by TA Instruments Japan Co., Ltd.), 0.01 to 0.02 g of sample is weighed into an aluminum pan, heated to 200°C, and cooled to 0°C at a rate of 10°C / min. The sample is then heated to 150°C at a rate of 10°C / min, and the endothermic peak is measured. The glass transition temperature is the temperature at the intersection of the extension of the baseline below the maximum endothermic peak temperature and the tangent line showing the maximum slope from the rising part of the peak to the top of the peak.
[0113] [Acid value of resin] Measurements are performed based on the method of JIS K 0070:1992, except that the measurement solvent is changed from the ethanol and ether mixture specified in JIS K 0070 to a mixture of acetone and toluene (acetone:toluene = 1:1 (volume ratio)) for amorphous resins, and a mixture of chloroform and dimethylformamide (chloroform:dimethylformamide = 7:3 (volume ratio)) for crystalline resins.
[0114] [Number average molecular weight and weight average molecular weight of resin] The number average molecular weight and the weight average molecular weight are determined by gel permeation chromatography (GPC) according to the following method. (1) Preparation of sample solution The resin is dissolved in tetrahydrofuran to a concentration of 0.5 g / 100 mL, and then the solution is filtered through a fluororesin filter (manufactured by Sumitomo Electric Industries, Ltd., product name: FP-200) with a pore size of 2 μm to remove insoluble components, thereby obtaining a sample solution. (2) Molecular weight measurement Using the following measuring device and analytical column, tetrahydrofuran is used as the eluent at a flow rate of 1 mL per minute, and the column is stabilized in a thermostatic bath at 40°C. 100 μL of the sample solution is injected into the column for measurement. The molecular weight of the sample is calculated based on a calibration curve that has been prepared in advance. The calibration curve used here includes several types of monodisperse polystyrene (Tosoh Corporation; 2.63 × 10 3 , 2.06×10 4 , 1.02×10 5 , GL Sciences Inc.; 2.10 x 10 3 , 7.00×10 3 , 5.04×10 4 ) is used as a standard sample. Measuring device: CO-8010 (product name, manufactured by Tosoh Corporation) Analytical column: GMH XL +G3000H XL (All are product names, manufactured by Tosoh Corporation)
[0115] [PET IV value] The viscosity can be determined by dissolving the material in a mixed solvent of phenol / tetrachloroethane (mass ratio) of 60 / 40 at a concentration of 4 g / L, measuring with an Ubbelohde viscometer, and calculating according to the following formula. IV=(-1+√(1+4kη)) / (2kC) (In the formula, k = 0.33, C = 0.004 g / mL, and η = (t1 / t0)-1 (t0: number of seconds for the solvent alone to fall, t1: number of seconds for the sample solution to fall).)
[0116] [Melting point of release agent] Using a differential scanning calorimeter "Q100" (manufactured by TA Instruments Japan, Inc.), 0.02 g of sample is weighed into an aluminum pan, heated to 200°C, and then cooled from 200°C to 0°C at a rate of 10°C / min. The sample is then heated at a rate of 10°C / min, the amount of heat is measured, and the maximum endothermic peak temperature is taken as the melting point.
[0117] [Average particle size of external additives] The average particle size refers to the number-average particle size, and is calculated by measuring the particle sizes (average of major and minor diameters) of 500 particles in a scanning electron microscope (SEM) photograph and averaging these by number.
[0118] [Volume Median Particle Size and CV Value of Resin Particles, Colorant Particles, and Release Agent Particles] (1) Measuring device: Laser diffraction type particle size measuring device "LA-920" (manufactured by Horiba, Ltd.) (2) Measurement conditions: Put the sample dispersion in a measurement cell, add distilled water, and measure the volume median particle size (D 50 ) and the volume average particle size are measured. The CV value is calculated according to the following formula. CV value (%) = (Standard deviation of particle size distribution / Volume average particle size) x 100
[0119] [Solid Content Concentration of Resin Dispersion, Colorant Dispersion, and Release Agent Dispersion] Using an infrared moisture meter "FD-230" (Kett Electric Laboratory Co., Ltd.), 5 g of the measurement sample is dried at a drying temperature of 150°C and measurement mode 96 (monitoring time 2.5 minutes, fluctuation range 0.05%), and the moisture content (mass%) of the dispersion is measured. The solid content concentration is calculated according to the following formula. Solid concentration (mass%) = 100-moisture (mass%)
[0120] [Volume Median Particle Size of Agglomerated Particles] Measuring instrument: "Coulter Multisizer (registered trademark) III" (manufactured by Beckman Coulter, Inc.) Aperture diameter: 50μm Analysis software: "Multisizer (registered trademark) III version 3.51" (Beckman Coulter, Inc.) Electrolyte: "Isoton (registered trademark) II" (manufactured by Beckman Coulter, Inc.) Measurement conditions: The sample dispersion is added to 100 mL of the electrolyte to adjust the concentration so that the particle size of 30,000 particles can be measured in 20 seconds. Then, 30,000 particles are measured and the volume median particle size (D 50 ) is required.
[0121] [Volume median particle size of toner (D 50 )〕 Measuring instrument: "Coulter Multisizer (registered trademark) III" (manufactured by Beckman Coulter, Inc.) Aperture diameter: 50μm Analysis software: "Multisizer (registered trademark) III version 3.51" (Beckman Coulter, Inc.) Electrolyte: "Isoton (registered trademark) II" (manufactured by Beckman Coulter, Inc.) Dispersion liquid: Polyoxyethylene lauryl ether "Emulgen (registered trademark) 109P" (manufactured by Kao Corporation, HLB (Griffin) = 13.6) was dissolved in the electrolyte to adjust the concentration to 5% by mass. Dispersion conditions: 10 mg of the measurement sample is added to 5 mL of the dispersion liquid, and dispersed for 1 minute using an ultrasonic disperser (machine name: US-1, manufactured by SND Co., Ltd., output: 80 W). Then, 25 mL of electrolyte is added, and the mixture is further dispersed for 1 minute using the ultrasonic disperser to prepare a sample dispersion liquid. Measurement conditions: The sample dispersion was added to 100 mL of the electrolyte to adjust the concentration so that the particle size of 30,000 particles could be measured in 20 seconds. Then, 30,000 particles were measured, and the volume median particle size (D 50 ) is required.
[0122] [Circularity of fused particles] The circularity of the fused particles is measured under the following conditions. Measurement equipment: Flow-type particle image analyzer "FPIA-3000" (Sysmex Corporation) Preparation of dispersion: Prepare the sample dispersion by diluting it with deionized water so that the solids concentration becomes 0.001 to 0.05% by mass. Measurement mode: HPF measurement mode
[0123] [Toner Circularity] The circularity of the toner particles is measured under the following conditions. Measurement equipment: Flow-type particle image analyzer "FPIA-3000" (Sysmex Corporation) Electrolyte: "Isoton (registered trademark) II" (manufactured by Beckman Coulter, Inc.) Dispersion liquid: Polyoxyethylene lauryl ether "Emulgen (registered trademark) 109P" (manufactured by Kao Corporation, HLB (Griffin) = 13.6) was dissolved in the electrolyte to adjust the concentration to 5% by mass. Dispersion conditions: 10 mg of the measurement sample is added to 5 mL of the dispersion liquid, and dispersed for 1 minute using an ultrasonic disperser (machine name: US-1, manufactured by SND Co., Ltd., output: 80 W). Then, 25 mL of electrolyte is added, and the mixture is further dispersed for 1 minute using the ultrasonic disperser to prepare a sample dispersion liquid. Measurement mode: HPF measurement mode
[0124] Resin manufacturing example 1 The alcohol component, the carboxylic acid component other than isophthalic acid, the esterification catalyst and the esterification promoter shown in Tables 1 to 4 were placed in a 10-liter four-neck flask equipped with a nitrogen inlet tube, a dehydration tube equipped with a fractionating tube through which hot water of 98 ° C. was passed, a stirrer and a thermocouple, and the mixture was held at 180 ° C. for 1 hour under a nitrogen atmosphere, and then heated from 180 ° C. to 230 ° C. at 10 ° C. / h, and then polycondensed at 230 ° C. for 5 hours. Then, the mixture was cooled to 180 ° C., isophthalic acid was added, the mixture was held at 180 ° C. for 1 hour, and then heated from 180 ° C. to 230 ° C. at 10 ° C. / h, and then polycondensed at 230 ° C. for 2 hours. Furthermore, the reaction was continued at 230 ° C. under a reduced pressure of 10 kPa until the softening point shown in Tables 1 to 4 was reached, and amorphous polyester resins (resins AH1, AH4, AH7, AH12, AL1, AL6, and AL11) were obtained. The physical properties are shown in Tables 1 to 4.
[0125] Resin manufacturing example 2 The alcohol component, the carboxylic acid component other than isophthalic acid, PET, the esterification catalyst and the esterification promoter shown in Tables 1 to 4 were placed in a 10-liter four-neck flask equipped with a nitrogen inlet tube, a stirrer and a thermocouple, and the mixture was held at 180°C for 1 hour under a nitrogen atmosphere, then heated from 180°C to 230°C at 10°C / h, and polycondensed at 230°C for 5 hours. The mixture was then cooled to 180°C, isophthalic acid was added, the mixture was held at 180°C for 1 hour, then heated from 180°C to 230°C at 10°C / h, and polycondensed at 230°C for 2 hours. The reaction was continued at 230°C under a reduced pressure of 10 kPa until the softening points shown in Tables 1 to 4 were reached, and amorphous polyester resins (resins AH2, AH3, AH8 to AH11, AL2, AL3, AL7 to AL10) were obtained. The physical properties are shown in Tables 1 to 4.
[0126] Resin manufacturing example 3 The alcohol component, carboxylic acid component other than adipic acid, esterification catalyst and esterification promoter shown in Tables 1 and 3 were placed in a 10-liter four-neck flask equipped with a nitrogen inlet tube, a dehydration tube equipped with a fractionating tube through which hot water of 98 ° C. was passed, a stirrer and a thermocouple, and the mixture was held at 180 ° C. for 1 hour under a nitrogen atmosphere, and then heated from 180 ° C. to 230 ° C. at 10 ° C. / h, and then polycondensed at 230 ° C. for 5 hours. Thereafter, the mixture was cooled to 180 ° C., adipic acid was added, and the mixture was held at 180 ° C. for 1 hour, and then heated from 180 ° C. to 230 ° C. at 10 ° C. / h, and then polycondensed at 230 ° C. for 2 hours. Furthermore, the reaction was carried out at 230 ° C. under a reduced pressure of 10 kPa until the softening point shown in Tables 1 and 3 was reached, and amorphous polyester resins (resins AH5 and AL4) were obtained. The physical properties are shown in Tables 1 and 3.
[0127] Resin manufacturing example 4 The alcohol component, carboxylic acid component other than adipic acid and isophthalic acid, esterification catalyst and esterification promoter shown in Tables 1 and 3 were placed in a 10-liter four-neck flask equipped with a nitrogen inlet tube, a dehydration tube equipped with a fractionating tube through which hot water of 98 ° C. was passed, a stirrer and a thermocouple, and the mixture was held at 180 ° C. for 1 hour under a nitrogen atmosphere, and then heated from 180 ° C. to 230 ° C. at 10 ° C. / h, and then polycondensed at 230 ° C. for 5 hours. Thereafter, the mixture was cooled to 180 ° C., adipic acid and isophthalic acid were added, and the mixture was held at 180 ° C. for 1 hour, and then heated from 180 ° C. to 230 ° C. at 10 ° C. / h, and then polycondensed at 230 ° C. for 2 hours. Furthermore, the reaction was carried out at 230 ° C. under a reduced pressure of 10 kPa until the softening point shown in Tables 1 and 3 was reached, and amorphous polyester resins (resins AH6 and AL5) were obtained. The physical properties are shown in Tables 1 and 3.
[0128] [Table 1]
[0129] [Table 2]
[0130] [Table 3]
[0131] [Table 4]
[0132] Resin manufacturing example 5 The alcohol and carboxylic acid components shown in Table 5 were placed in a 10-liter four-neck flask equipped with a thermometer, a stainless steel stirring rod, a downflow condenser, and a nitrogen inlet tube, and the temperature was raised to 200°C over 8 hours in a nitrogen atmosphere in a mantle heater. An esterification catalyst was then added, and the reaction was carried out at 8.0 kPa until the softening points shown in Table 5 were reached, obtaining crystalline polyester resins (resins C1 to C3, C5 to C7). The physical properties are shown in Table 5.
[0133] Resin manufacturing example 6 The alcohol component, carboxylic acid component, and polymerization inhibitor shown in Table 5 were placed in a 10-liter four-neck flask equipped with a thermometer, a stainless steel stirring rod, a downflow condenser, and a nitrogen inlet tube, and the temperature was raised to 200°C over 8 hours in a nitrogen atmosphere in a mantle heater. An esterification catalyst was then added, and the reaction was carried out at 8.0 kPa until the softening point shown in Table 5 was reached, obtaining a crystalline polyester resin (resin C4). The physical properties are shown in Table 5.
[0134] [Table 5]
[0135] Examples 1 to 12, 15 to 19 and Comparative Examples 1 to 3 100 parts by mass of the binder resin shown in Table 6, 4 parts by mass of colorant "ECB-301" (manufactured by Dainichiseika Color & Chemicals Mfg. Co., Ltd., phthalocyanine blue (PB15:3)), 1 part by mass of negatively chargeable charge control agent "Bontron (registered trademark) S-34" (manufactured by Orient Chemical Industries Co., Ltd.), and 3 parts by mass of release agent "Carnauba Wax C1" (manufactured by Kato Yoko Co., Ltd., melting point: 83°C) were mixed in a Henschel mixer and then melt-kneaded under the conditions shown below.
[0136] The obtained mixture was melt-kneaded using a co-rotating twin screw extruder with a kneading section total length of 1560 mm, a screw diameter of 42 mm, and a barrel inner diameter of 43 mm at a screw rotation speed of 200 r / min and a barrel set temperature of 100° C. to obtain a melt-kneaded product. The mixture was fed at a rate of 20 kg / h and the average residence time was about 18 seconds.
[0137] The resulting kneaded product was cooled, and the resulting molten kneaded product was cooled and coarsely pulverized, then pulverized in a jet mill and classified using an airflow classifier (manufactured by Nippon Pneumatic Mfg. Co., Ltd.) to obtain a classified product.
[0138] Next, the resulting classified material was subjected to a spheronization process using a hot air spheronizer (manufactured by Nippon Pneumatic Mfg. Co., Ltd., product name: Meteor Rainbow) to obtain a volume median particle size (D50 ) was 7.0 μm. The spheronization conditions were as follows: the amount of unprocessed particles fed to the hot air spheronizer was 3.0 kg per hour, the amount of hot air supplied was 900 L per minute, the hot air temperature was 190°C, the pressure of the cooling air supplied was 0.15 MPa, and the amount of air supplied from the secondary air injection nozzle was 230 L per minute. The distance between the cooling air intake and the collision member was 2.0 cm.
[0139] 100 parts by mass of the obtained toner particles and 1.0 part by mass of hydrophobic silica "R972" (manufactured by Nippon Aerosil Co., Ltd., hydrophobic treatment agent: DMDS, average particle size: 16 nm) and 1.0 part by mass of hydrophobic silica "RY-50" (manufactured by Nippon Aerosil Co., Ltd., hydrophobic treatment agent: silicone oil, average particle size: 40 nm) as external additives were mixed in a Henschel mixer (manufactured by Nippon Coke and Kogyo Co., Ltd.) at 3000 r / min (circumferential speed: 32 m / s) for 3 minutes to obtain a toner.
[0140] Example 13 A toner was obtained in the same manner as in Example 1, except that the release agent "Carnauba wax C1" was not used.
[0141] Comparative Example 4 A toner was obtained in the same manner as in Example 1, except that the sphering process after obtaining the classified product was performed by mechanical processing. That is, in the sphering process, instead of a hot air type sphering device (manufactured by Nippon Pneumatic Mfg. Co., Ltd., product name: Meteor Rainbow), a surface modification device equipped with a hammer and a liner, Faculty "F430 type" (manufactured by Hosokawa Micron Corp.), whose raw material inlet was modified so as to introduce the treated material into the second space, was used, and the dispersion rotation speed was 5100 r / min, the classification rotation speed was 5200 r / min, and the air volume was 20 Nm 3 The spheronization process was carried out under the following conditions: 12 hammers, input amount of 750 g, mixing time of 60 seconds.
[0142] Comparative Example 5 [Emulsification aggregation method] <Preparation of aqueous dispersion of core resin particles> 600g of methyl ethyl ketone was put into a 5-liter container equipped with a stirrer, reflux condenser, dropping funnel, thermometer and nitrogen inlet tube, and 123g (45 parts by mass) of resin AH1 and 27g (10 parts by mass) of resin C1 were added at 60°C and dissolved. 5% by mass of sodium hydroxide aqueous solution was added to the obtained solution so that the degree of neutralization was 60 mol% with respect to the acid value of the resin, and the mixture was stirred for 30 minutes to obtain a mixture. Then, 675g of deionized water was added over 77 minutes. Next, while stirring at 250r / min, methyl ethyl ketone was distilled off at a temperature of 50°C or less under reduced pressure, and the solid content concentration of the aqueous dispersion was measured, and the solid content concentration of the aqueous dispersion was adjusted to 20% by mass with deionized water to obtain a core resin dispersion. The volume median particle size (D 50 ) was 200 nm and the CV value was 24%.
[0143] <Preparation of Aqueous Dispersion of Shell Resin Particles> 600g of methyl ethyl ketone was placed in a 5-liter container equipped with a stirrer, reflux condenser, dropping funnel, thermometer, and nitrogen inlet tube, and 150g of resin AL1 was added at 60°C and dissolved. A 5% by mass aqueous solution of sodium hydroxide was added to the obtained solution so that the degree of neutralization was 60 mol% relative to the acid value of the resin, and the mixture was stirred for 30 minutes to obtain a mixture. Subsequently, 675g of deionized water was added over 77 minutes. Next, while stirring at 250 r / min, methyl ethyl ketone and a part of the water were distilled off at a temperature of 50°C or less under reduced pressure, and the solid content concentration of the aqueous dispersion was measured, and the solid content concentration of the aqueous dispersion was adjusted to 20% by mass with deionized water to obtain a shell resin dispersion. The volume median particle size (D 50 ) was 110 nm and the CV value was 20%.
[0144] <Preparation of Colorant Dispersion> In a 1-liter beaker, 116.2 g of colorant "ECB-301" (Dainichiseika Color & Chemicals Mfg. Co., Ltd., Phthalocyanine Blue (PB15:3)), 154.9 g of anionic surfactant "Neopelex (registered trademark) G-15" (Kao Corporation, 15% by mass aqueous solution of sodium dodecylbenzenesulfonate) and 260 g of deionized water were mixed and dispersed at room temperature for 3 hours using a homogenizer, and then deionized water was added so that the solids concentration became 24% by mass, thereby obtaining a colorant dispersion. The volume median particle diameter (D 50 ) was 118 nm and the CV value was 27%.
[0145] <Preparation of release agent dispersion> 50 g of Fischer-Tropsch wax (manufactured by Nippon Seiro Co., Ltd., trade name: FNP0090, melting point: 90°C), 5 g of a cationic surfactant (manufactured by Kao Corporation, trade name: Sanisol B50) and 200 g of deionized water were heated to 95°C, and the paraffin wax was dispersed using a homogenizer, followed by dispersion processing using a pressure discharge homogenizer to obtain a release agent dispersion liquid with a solid content concentration of 20 mass%. The volume median particle diameter (D 50 ) was 550 nm and the CV value was 26%.
[0146] <Preparation of Toner Particles> In a 3-liter four-neck flask equipped with a dehydration tube, a stirrer, and a thermocouple, 500 g of the core resin dispersion, 36 g of the colorant dispersion, 33 g of the release agent dispersion, and 3.3 g of a 15% by mass aqueous solution of sodium dodecylbenzenesulfonate "Neopelex G-15" (manufactured by Kao Corporation, an anionic surfactant) were mixed at a temperature of 25° C. Next, while stirring the resulting mixture, a solution obtained by dissolving 40 g of ammonium sulfate in 570 g of deionized water and adding a 4.8% by mass aqueous solution of potassium hydroxide to adjust the pH to 8.2 was dropped over 10 minutes at 25° C., and the temperature was then raised to 62° C. over 2 hours to measure the volume median particle diameter (D 50 The temperature was maintained at 62° C. until the particle size reached 6.9 μm, thereby obtaining a dispersion of aggregated particles (I).
[0147] While maintaining the temperature of the obtained dispersion of aggregated particles (I) at 62° C., 410 g of the shell resin dispersion was added dropwise at a rate of 0.6 mL / min (0.6 g / min) to obtain a dispersion of aggregated particles (II). 50 ) was 7.0 μm.
[0148] To the dispersion of the obtained aggregated particles (II), an aqueous solution of 20 g of sodium polyoxyethylene lauryl ether sulfate "EMAL E-27C" (manufactured by Kao Corporation, anionic surfactant, effective concentration 27% by mass), 280 g of deionized water, and 40 g of 0.1 mol / L aqueous sulfuric acid solution was added. The temperature was then raised to 80°C over 1 hour, and the mixture was kept at 80°C for 30 minutes, after which 10 g of 0.1 mol / L aqueous sulfuric acid solution was added, and the mixture was further kept at 80°C for 15 minutes. Thereafter, 15 g of 0.1 mol / L aqueous sulfuric acid solution was added again, and the mixture was kept at 80°C until the circularity reached 0.972, thereby obtaining a dispersion of fused particles in which the aggregated particles were fused (core-shell particle dispersion).
[0149] The obtained core-shell particle dispersion was cooled to 30°C, and the dispersion was filtered under suction to separate the solid content, which was then washed with deionized water at 25°C and filtered under suction for 2 hours at 25°C. The solid content was then vacuum dried at 33°C for 24 hours using a vacuum constant temperature dryer "DRV622DA" (manufactured by ADVANTEC) to obtain toner particles. The particle size of the obtained toner particles was 7.0 μm and the circularity was 0.972. The composition ratio of the binder resin of the obtained toner particles was resin AH1 / resin AL1 / resin C1=45 / 45 / 10.
[0150] 100 parts by mass of the obtained toner particles and 1.0 part by mass of hydrophobic silica "R972" (manufactured by Nippon Aerosil Co., Ltd., hydrophobic treatment agent: DMDS, average particle size: 16 nm) and 1.0 part by mass of hydrophobic silica "RY-50" (manufactured by Nippon Aerosil Co., Ltd., hydrophobic treatment agent: silicone oil, average particle size: 40 nm) as external additives were mixed in a Henschel mixer (manufactured by Nippon Coke and Kogyo Co., Ltd.) at 3000 r / min (circumferential speed: 32 m / s) for 3 minutes to obtain a toner.
[0151] Comparative Example 6 A toner was obtained in the same manner as in Comparative Example 5, except that in the step of obtaining a core-shell particle dispersion, the temperature was kept at 80° C. until the circularity of the core-shell particles reached 0.960.
[0152] Example 14 50 parts by mass of the toner particles obtained in Comparative Example 5 and 50 parts by mass of the toner particles obtained in Comparative Example 6 were mixed in a Henschel mixer (manufactured by Nippon Coke and Engineering Co., Ltd.) at 3000 r / min (circumferential speed 32 m / s) for 3 minutes to obtain a volume median particle size (D 50 ) of 7.0 μm and a circularity of 0.965.
[0153] 100 parts by mass of the obtained toner particles and 1.0 part by mass of hydrophobic silica "R972" (manufactured by Nippon Aerosil Co., Ltd., hydrophobic treatment agent: DMDS, average particle size: 16 nm) and 1.0 part by mass of hydrophobic silica "RY-50" (manufactured by Nippon Aerosil Co., Ltd., hydrophobic treatment agent: silicone oil, average particle size: 40 nm) as external additives were mixed in a Henschel mixer (manufactured by Nippon Coke and Kogyo Co., Ltd.) at 3000 r / min (circumferential speed: 32 m / s) for 3 minutes to obtain a toner.
[0154] 1 shows a graph illustrating the circularity distribution of the toners obtained in Example 1 and Comparative Examples 4 and 5. From this graph, it can be seen that Example 1, in which toner particles were obtained by a melt kneading method and hot air treatment, gave toner particles with a wide circularity distribution, compared to Comparative Example 4, in which toner particles were made spherical by a mechanical treatment, and Comparative Example 5, in which toner particles were made spherical by an emulsion aggregation method.
[0155] Test Example 1 [Charge Stability of Toner] Under conditions of a temperature of 25°C and a relative humidity of 50%, 0.6 g of toner and 19.4 g of silicone ferrite carrier (manufactured by Kanto Denka Kogyo Co., Ltd., average particle size 90 μm) were placed in a 50 mL polyethylene container and mixed using a ball mill at 250 r / min. The charge amount of the toner was measured using a Q / M meter (manufactured by EPPING Co., Ltd.) using the following method. After a specified mixing time, a specified amount of the mixture of toner and carrier was put into a cell attached to the Q / M meter, and only the toner was sucked through a sieve with 32 μm openings (stainless steel, twill weave, wire diameter: 0.0035 mm) for 90 seconds. The voltage change on the carrier that occurred at that time was monitored, and the value of [total amount of electricity after 90 seconds (μC) / amount of sucked toner (g)] was taken as the charge amount (μC / g). The ratio α of the charge amount after 60 seconds of mixing to the charge amount after 600 seconds of mixing (charge amount after 60 seconds of mixing / charge amount after 600 seconds of mixing) was calculated to evaluate the charge stability. The results are shown in Table 7. The larger the value, the better the charge stability.
[0156] Test Example 2 [Toner Transferability] The toner was loaded into a color printer "MICROLINE 5400" (product name, manufactured by Oki Electric Industry Co., Ltd.) and a solid image was printed. At this time, the amount of toner on the photoreceptor for the solid image was 0.40 to 0.50 mg / cm. 2 The machine was stopped midway through printing a solid image, mending tape was applied to the photoconductor after it had passed the transfer section, and the toner remaining on the photoconductor without being transferred was transferred to the mending tape, and the mending tape was then peeled off from the photoconductor. The hue difference between the peeled off mending tape and an unused mending tape was measured using a color difference meter "X-Rite" (product name, manufactured by X-Rite Corporation), and the transferability (transfer efficiency) was evaluated based on the color difference density ΔE. The results are shown in Table 7. The smaller the ΔE value, the higher the transferability.
[0157] Test Example 3 [Toner Durability] The toner was loaded onto a printer called "Page Presto N-4" (Casio Computer Co., Ltd., fixing: contact fixing method, development: non-magnetic one-component development method, developer roll diameter: 2.3 cm), and a pattern of diagonal stripes with a blackening rate of 5.5% was continuously printed in an environment of 32°C temperature and 85% relative humidity. A black solid image was printed every 500 sheets during the printing, and the presence or absence of streaks on the image was confirmed. Printing was stopped when streaks appeared on the image, and printing was continued up to a maximum of 9000 sheets. The number of sheets printed up to the point where streaks were visually observed on the image was regarded as the number of sheets on which streaks appeared due to the toner fusing and adhering to the developer roll, and durability was evaluated. The results are shown in Table 7. In the table, ">9000" means that no streaks appeared even on the 9000th sheet. The greater the number of sheets on which streaks did not appear, the higher the durability of the toner.
[0158] [Table 6]
[0159] [Table 7]
[0160] From the above results, it is found that both the charging stability and transferability are good, and the durability is also good in Examples 1 to 19. In particular, it is found that the durability is excellent when the amorphous polyester resin A is a polycondensation product using polyethylene terephthalate (PET) together with an alcohol component and a carboxylic acid component, as in Examples 8, 9, and 15 to 18. In contrast, it can be seen from Comparative Examples 1 to 6 that a small proportion of toner particles with a high degree of circularity results in poor transferability, and a small proportion of toner particles with a low degree of circularity results in poor charging stability. In particular, Comparative Examples 1 and 2, which use a crystalline polyester resin with an ester group concentration and / or melting point outside the specified range, have a small proportion of toner particles with a high degree of circularity and are poor in charging stability, while Comparative Example 3, which uses an amorphous polyester resin with a small amount of short-chain aliphatic diol, has a small proportion of toner particles with a low degree of circularity and are poor in transferability. [Industrial Applicability]
[0161] The toner for developing electrostatic images of the present invention is suitably used for developing latent images formed in electrophotography, electrostatic recording, electrostatic printing and the like.
Claims
1. A toner for developing electrostatic images, comprising a crystalline polyester resin C and an amorphous polyester resin A, wherein the crystalline polyester resin C has an ester group concentration of 6.5 mmol / g or more and 10.0 mmol / g or less and a melting point of 65°C or more and 105°C or less, the alcohol component of the amorphous polyester resin A contains 80 mol% or more of an aliphatic diol having 2 to 5 carbon atoms, the toner for developing electrostatic images has an average circularity of 0.955 or more and 0.975 or less, a relative frequency of the circularity of 0.920 to 0.960 is 30% or more and 40% or less, and a relative frequency of the circularity of 0.970 to 0.990 is 25% or more and 35% or less.
2. 2. The toner for developing electrostatic images according to claim 1, wherein a mass ratio of the crystalline polyester resin C to the amorphous polyester resin A is 3 / 97 or more and 30 / 70 or less.
3. 3. The toner for developing electrostatic images according to claim 1 or 2, wherein the carboxylic acid component of the amorphous polyester resin A contains two kinds selected from the group consisting of terephthalic acid or a terephthalic acid alkyl ester having 1 to 3 carbon atoms in the alkyl group, isophthalic acid or an isophthalic acid alkyl ester having 1 to 3 carbon atoms in the alkyl group, and phthalic acid or a phthalic acid alkyl ester having 1 to 3 carbon atoms in the alkyl group.
4. 3. The toner for developing electrostatic images according to claim 1, wherein the alcohol component of the amorphous polyester resin A contains ethylene glycol and neopentyl glycol.
5. 3. The toner for developing an electrostatic image according to claim 1, which comprises toner particles and an external additive, and the toner particles are hot air treated products.
6. 3. The toner for developing electrostatic images according to claim 1, wherein the amorphous polyester resin A is a polycondensation product of an alcohol component, a carboxylic acid component and polyethylene terephthalate.
7. a relative frequency of the circularity of the toner of 0.970 to 0.990 being from 25% to 35%; and a process for producing a toner for developing electrostatic images comprising: a step of melt-kneading a mixture containing the crystalline polyester resin C and the amorphous polyester resin A; a step of pulverizing the kneaded mixture; a step of classifying the pulverized product; and a step of subjecting the classified product to a hot-air treatment.
Citation Information
Patent Citations
Toner, and two-component developer
JP2009294374A
Toner and method for manufacturing the same, and two-component developer including the same
JP2020086288A